Evaluation of antimicrobial activity exploration of the leaves extracts of Borreria articularis (Linn. F.) - Azad, Abdul Kalam; Wan Sulaiman, Wan Mohd. Azizi; Tengku Zakaria, Tengku Muhammad Faris (Academic Journals, 2013)
In this study the plant of Borreria articularies (Linn. F) (family Rubiaceae) were subjected for phytochemical, antibacterial and antifungal evaluations. The sample powder was subjected to cold maceration by ethanol and methanol for 48 h at room temperature, concentrated by using a rotary vacuum evaporator (BUCHI R-205) and drying at −50 °C using bench top freeze dryer (ALPHA 1-4LD-2) and then kept in the fridge (4°C). Compound identification by comparing the NIST library data of the peaks with those reported in mass spectra of the peaks with literature data. The in vitro antimicrobial activities were determined by disc diffusion method and poisoned food technique respectively. Mueller- Hinton and Sabouraud medium was used for culture of bacteria and fungi. 5% ethanolic solution of the crude extracts and pure compound were used as the test material. The studies revealed that alkaloids, glycosides, tanins, flavonoids, saponins and reducing sugars are present in both the extracts. The pure compound, 6-methyl-5-cyclodecen-1-ol, exhibited good antimicrobial activity against all the pathogens tested. The highest zone of inhibition 20 mm was exhibited by ethanol and 6-methyl-5-cyclodecen-1-ol at a concentration of 2,000 μg/disc against both Escherichia coli and Vibrio cholera. The highest inhibition observed was 55.17 and 53.33% of fungal radial mycelial growth at a concentration of (100 μg/ml) against Aspergillus ustus and Aspergillus ochraceus respectively. The extracts exhibited antimicrobial activity which could serve as an alternative traditional medicine for treatment as antimicrobial agent. Keywords: Borreria articularis (Linn. F), 6-methyl 5-cyclodecen-1-ol, phytochemical screening, antimicrobial activity.